2017
DOI: 10.1111/jsr.12509
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported sleep quantity, quality and sleep hygiene in elite athletes

Abstract: SUMMARYSleep is essential for recovery and performance in elite athletes. While actigraphy-based studies revealed suboptimal sleep in athletes, information on their subjective experience of sleep is scarce. Relatively unexplored is also the extent to which athletes' sleep is adversely affected by environmental conditions and daytime behaviours, that is sleep hygiene. This study aimed to provide insight in sleep quantity, quality and its putative association with sleep hygiene. Participants were 98 elite (youth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
76
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 33 publications
8
76
0
1
Order By: Relevance
“…However, there is a high prevalence of insomnia symptoms among athletes 9. Much of the research examining athletes’ sleep has been derived from subjective tools (eg, diaries) 12. This is a problem because subjective tools, while useful for monitoring large cohorts, typically correlate poorly with objective data 13…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a high prevalence of insomnia symptoms among athletes 9. Much of the research examining athletes’ sleep has been derived from subjective tools (eg, diaries) 12. This is a problem because subjective tools, while useful for monitoring large cohorts, typically correlate poorly with objective data 13…”
Section: Introductionmentioning
confidence: 99%
“…It was rather unexpected that values of day-to-day HRV (lnRMSSD) did not correlate with the duration of night sleep. Sleep is indispensable for recovery and performance progress in athletes [36,37]. It is well established that the autonomic nervous system plays an important role in the modulation of cardiovascular functions during the onset of sleep and in transition between sleep phases [38].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, there has been a large increase in research surrounding the sleep profiles of athletes (16,22), and the health and performance consequences of sleep disturbances (9,39). Such research has shown that athletes are liable to suffer reduced sleep quantity and quality (16,22,32), which can lead to decrements in sporting performance (7,23), increased risk of illness (6) and deviations in wellbeing measures (19,27). These findings have resulted in practitioners commonly including measures of perceived sleep quality in daily wellbeing questionnaires aimed at monitoring their athletes (2,24,40).…”
Section: Introductionmentioning
confidence: 99%